Spanning BODIPY fluorescence with self-assembled micellar clusters - Solomonov, Aleksei V.; Marfin, Yuriy S.; Tesler, Alexander; Merkushev, Dmitry A.; Bogatyreva, Elizaveta A.; Antina, Elena V.; Rumyantsev, Evgeniy V.; Shimanovich, Ulyana (Colloids and Surfaces B: Biointerfaces, 2022)
BODIPY dyes possess favorable optical properties for a variety of applications including in vivo and in vitro diagnostics. However, their utilization might be limited by their water insolubility and incompatibility with chemical modifications, resulting in low aggregation stability. Here, we outline the route for addressing this issue. We have demonstrated two approaches, based on dye entrapment in micellar coordination clusters (MCCs); this provides a general solution for water solubility as well as aggregation stability of the seven BODIPY derivatives. These derivatives have various bulky aromatic substituents in the 2,3,5,6- and meso-positions and can rotate relative to a dipyrrin core, which also provides molecular rotor properties. The molecular structural features and the presence of aromatic groups allows BODIPY dyes to be used as "supporting molecules", thus promoting micelle-micelle interaction and micellar network stabilization. In the second approach, self-micellization, following BODIPY use, leads to MCC formation without the use of any mediators, including chelators and/or metal ions. In both approaches, BODIPY exhibits an excellent optical response, at a concentration beyond its solubilization limit in aqueous media and without undesired crystallization. The suggested approaches represent systems used to encapsulate BODIPY in a capsule-based surfactant environment, enabling one to track the aggregation of BODIPY; these approaches represent an alternative system to study and apply BODIPY's molecular rotor properties. The stabilized compounds, i.e., the BODIPY-loaded MCCs, provide a unique feature of permeability to hydrophilic ligand-switching proteins such as BSA; they exhibit a bright “turn-on” fluorescence signal within the clusters via macromolecular complexation, thus expanding the possibilities of water-soluble BODIPY-loaded MCCs utilization for functional indicators.
CRIS-Team Scopus Importer:2022-05-20
Keywords: BODIPY dyes; Encapsulation; Micellar clusters; Proteins; Self-assembly; Surfactants